Menganalisis Hubungan Pakan Ikan Hasil Biodegradasi Styrofoam Oleh Ulat Hongkong Terhadap Nilai LD50 Dengan Variasi Komposisi Bahan Pakan Ikan - Zahra Nadia Elysahaq; Elvi Yenie; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Styrofoam is the number 6 plastic in the plastic classification, namely polystyren and styrofoam is categorized as the 5th largest producer of hazardous waste in the world. One method of processing styrofoam waste is biodegradation using mealworm (Tenebrio molitor larvae) because it is able to degrade styrofoam and does not have a negative impact on survival. The research aims to analyze the relationship of pellet from the biodegradation of styrofoam by mealworm to LD50 values with variations in the composition of pellet making. This research was carried out by the experimental method. The results of the biodegradation of styrofoam produce waste are fecula (mealworm feces) and biomass (dead mealworms). Variations in the composition ratio of ingredients in the pellets of each basin are different. Treatment of A = pellets P1 (25% biomass and 75% fecula), B = P2 pellets (50% biomass and 50% fecula), C = P2 pellets (75% biomass and 25% fecula), and D = pellets commercial buoyancy as a control. The results of the LD50 toxicity test on parrot fish, pellet from the biodegradation of styrofoam by mealworm is not toxic.Keywords: styrofoam waste, biodegradation, mealworm, pellet, LD50 toxicity test.